Calpain-cleaved type 1 inositol 1,4,5-trisphosphate receptor impairs ER Ca(2+) buffering and causes neurodegeneration in primary cortical neurons - Kopil, Catherine M. (J Neurochem, 2012)
Disruption of neuronal Ca(2+) homeostasis plays a well-established role in cell death in a number of neurodegenerative disorders. Recent evidence suggests that proteolysis of the type 1 inositol 1,4,5-trisphosphate receptor (InsP R1), a Ca(2+) release channel on the endoplasmic reticulum, generates a dysregulated channel, which may contribute to aberrant Ca(2+) signaling and neurodegeneration in disease states. However, the specific effects of InsP(3)R1 proteolysis on neuronal Ca(2+) homeostasis are unknown, as are the functional contributions of this pathway to neuronal death. This study evaluates the consequences of calpain-mediated InsP(3)R1 proteolysis on neuronal Ca(2+) signaling and survival using adeno-associated viruses to express a recombinant cleaved form of the channel (capn-InsP(3)R1) in rat primary cortical neurons. Here, we demonstrate that expression of capn-InsP(3)R1 in cortical cultures reduced cellular viability. This effect was associated with increased resting cytoplasmic Ca(2+) concentration ([Ca(2+)](i)), increased [Ca(2+)](i) response to glutamate, and enhanced sensitivity to excitotoxic stimuli. Together, our results demonstrate that InsP(3)R1 proteolysis disrupts neuronal Ca(2+) homeostasis, and potentially acts as a feed-forward pathway to initiate or execute neuronal death.